Sarcopenia: revised European consensus on definition and diagnosis - Cruz-Jentoft, Alfonso J.; Bauer, Jürgen M. (Age & ageing, 2019)
AbstractBackground. in 2010, the European Working Group on Sarcopenia in Older People (EWGSOP) published a sarcopenia definition that aimed to foster advances